Last-mile logistics with alternative delivery locations: A systematic literature review - Nima Pourmohammadreza; Mohammad Reza Akbari Jokar; Tom Van Woensel (Results in Engineering)
Last-mile logistics plays a crucial role in modern supply chains, particularly in the retail industry. Despite its vital role in ensuring timely delivery to end-users, it is often considered the most expensive and ineffective segment of the logistics chain. More than just a financial burden, last-mile logistics poses significant environmental challenges and can be a source of negative social externalities, impacting customer satisfaction and retention. This paper presents a systematic and bibliometric analysis of 257 academic publications on the evolving domain of last-mile logistics, emphasizing emerging trends in Alternative Delivery Locations (ADL), using Scopus and Web of Science data. Employing the theory refinement approach, we analyze and refine existing SCM frameworks to understand and enhance last-mile logistics with innovative and sustainable delivery solutions. Over 89 % of these articles were published in the past six years, reflecting the growing prominence of sustainable and innovative delivery solutions like parcel lockers, roaming delivery points, and mobile distribution mechanisms. The findings reveal that adopting ADL enhances customer satisfaction by addressing critical delivery challenges such as flexibility and sustainability. This review provides actionable insights for practitioners, emphasizing the importance of integrating ADL into last-mile strategies to reduce costs, minimize environmental impact, and improve operational efficiency. Retailers can leverage these insights to align delivery systems with evolving consumer expectations and sustainability goals, ensuring competitiveness in a rapidly changing marketplace.